Legal Protection of Intellectual Property Rights in the Digital Industry: A Review of Legal Developments and Implementation Challenges - Anam, Khoirul (West Science Law and Human Rights, 2024)
This research aims to understand the Legal Protection of Intellectual Property Rights in the Digital Industry: A Review of Legal Developments and Implementation Challenges.The literature study will also include a review of relevant legal literature, especially relating to intellectual property protection in the digital era. In addition, legal sources related to IPR in the digital era are also an important basis for this analysis, ensuring a deep understanding of the existing regulatory framework. By utilizing the latest literature and relevant legal sources, this research can provide a comprehensive understanding of the challenges, trends and solutions in protecting IPR amidst the dynamics of digital technology. Research results Legal protection of intellectual property rights (IPR) in the digital era is a complex and vital issue that requires a holistic approach. Challenges include copyright infringement, data security, and global competition for patents and trademarks. Strong and effective regulations are needed to address these challenges without stifling innovation and economic growth. Awareness of the importance of intellectual property rights must be increased through extensive educational campaigns and programs by increasing their understanding of copyright, patents, trademarks and industrial designs, individuals will play a greater role in respecting and protecting intellectual property rights in the digital era.